أثر نمط القيادة الإدارية في الروح المعنوية للموظفين في وزارة التعليم العالي السورية - ريا, ثراء (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى التعرّف على أنماط القيادة بشكل عام ونمط القيادة المتبع في وزارة التعليم العالي السورية بشكل خاص ومدى تأثير هذا النمط على الروح المعنوية للموظفين لدى هذه الجهة.تكونت عيّنة البحث من مئتين وخمسة عشر موظفاً وموظفة من مختلف المستويات الإدارية في وزارة التعليم العالي السورية وتم استخدام مقياس (Bass & Avolio,1995) لقياس النمط القيادي المتبع، ومقياس ( البلبيسي 2013 ) لقياس الروح المعنوية .كما تم استخدام وسائل إحصائية مناسبة بقصد تحليل الاستبانات التي تم توزيعها على عيّنة الدراسة لاختبار العلاقة المعنوية لمتغيرات الدراسة باستخدام برنامج SPSS- Statistical Package for Social Science .توصل البحث إلى أن النمط القيادي المتبع في هذه الوزارة هو نمط القيادة التحويلي يليه نمط القيادة التبادلي (الإجرائي) وأخيراً النمط السلبي بحيث تُؤثر هذه الأنماط جميعها وبدرجات متفاوتة على الروح المعنوية للموظفين واندفاعهم نحو العمل باعتبار أن النسب المئوية لتوافر هذه الأنماط جاءت متقاربة جداً، الأمر الذي يمكن تفسيره باتباع القادة الإداريين في هذه الوزارة لجميع أنماط القيادة الإدارية حسب الحال.This research aims to identify the leadership styles in general and the established pattern of leadership in the Syrian Ministry of Higher Education in particular, and the impact of this pattern on the morale of the employees of this party.The research sample consisted of two hundred and fifteen male and female employees of various administrative levels in the Syrian Ministry of Higher Education and (Bass & Avolio, 1995) were used to measure the pattern of the leadership, and the (Bilbeisi 2013) to measure the morale.They have used the statistical methods which were suitable for the purpose of the questionnaires that were distributed to the study sample to examine the moral relationship to the variables of the study using the Statistical Package SPSS which is a program analysis for Social Science.The final result of the research is that the used pattern of the leadership in this Ministry is the transformational leadership pattern, followed by the interactive leadership pattern (procedural) and finally the negative pattern, which eventually effect the staff morale in various degrees and their keenness to work, considering that the percentages of compatibility of these patterns came too close together, which can explain or prove that the Administrative leaders in this Ministry; follow all administrative patterns of leadership depending on each case.